Robotic correction of iatrogenic ureteral stricture: preliminary experience from a tertiary referral centre. (3rd September 2019) - Masieri, L.; Sforza, S.; Di Maida, F.; Grosso, Antonio Andrea; Mari, A.; Rosi, Emma Maria; Tellini, R.; Carini, M.; Minervini, A.
Abstract: Objective: Iatrogenic stenosis is a relatively common complication and it could happen after urological procedures in the entire course of the ureter. The aim of this study is to report the surgical outcomes of 36 consecutive patients (period April 2013–November 2018) submitted to robot-assisted correction of benign stricture with previous urological surgery in a tertiary referral center. Methods: Elective criteria were to have had a benign ureteral stricture development after at least one urological procedure. Patients were classified as failures in the event of post-operative ultrasound demonstrating persistent hydronephrosis with or without symptoms or persistent symptoms with renal scan evidence of obstruction or redo procedures. Results: Eighteen patients (50%) were treated for calculosis, seven (19.4%) patients were submitted to double J ureteral stenting and previous pyeloplasty was performed in 11 (30.5%) patients. Overall median operative time was 160 min (IQR = 120–180). Five (13.8%) complications with three (8.3%) surgical post-operative complications occurred. Length of stay was 6 (IQR = 5–7) days. At last follow-up, ranging between 7–60 months, the overall success rate was 86.1% (31/36): three of them (8.3%) were submitted to retrograde holmium laser endopyelotomy, while two (5.5%) underwent a redo robot-assisted correction. Conclusions: Robot-assisted correction procedures can be done safely with good perioperative outcomes and a high post-operative success rate in a tertiary referral center. Further randomized clinical trials are mandatory to confirm the safety of this procedure.